Understanding history 1 for grade 6 - Riaz, Ismat (Karachi Oxford university press, 2023)
"Understanding History 1" by Oxford University Press is a comprehensive textbook designed for Grade 6 students. It introduces young learners to the key concepts, events, and figures that have shaped history. The book covers various civilizations, timelines, and the importance of historical inquiry, encouraging critical thinking and engagement with the past. Through a blend of narratives, illustrations, and activities, it aims to foster an appreciation for history while building foundational knowledge that students can build upon in higher grades.